Application of biological traits to further our understanding of the impacts of dredged material disposal on benthic assemblages. Issue 1 (15th April 2016) - Bolam, S.G.; McIlwaine, P.S.O.; Garcia, C.
Abstract: While the effects of coastal disposal of dredged material on benthic assemblage structure have been well studied, our understanding of the mechanism of such responses, and their potential ecological implications, remain relatively unknown. Data from a licenced disposal site off the northeast coast of England are analysed to address this and improve our ability to make informed licencing decisions for this activity. Assemblages within the disposal site displayed reduced number of species and total invertebrate density, an altered assemblage taxonomic structure, and a shift towards a greater numerical dominance of less-productive individuals. Following separate analyses of biological response and effect traits, a novel approach for marine benthic trait analysis, we identify the traits responsible (i.e. response traits) for the observed structural alterations. Furthermore, analysis of the effect traits revealed that the assemblages characterising the disposal site possess a greater bioturbative capability compared to those not directly impacted by disposal. Highlights: Benthic community structure was impacted by dredge material disposal. Alterations to taxonomic composition reduced secondary production. Response and effect traits were separated prior to Biological Traits Analysis. This novel trait approach provided an improved assessment of functional change.